Ameliorative effect of Borago officinalis L extract on sperm parameters, testosterone level in a streptozotocin-induced mouse model of diabetes - Nabaz abasi; shiva khalesro; Erfan daneshi (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: Diabetes mellitus (DM) is a common metabolic disease characterized by high blood sugar levels. It is well known that men with diabetes frequently experience reproductive disorders and sexual dysfunction. In fact, sperm quality has a significant impact on fertilization success and embryo development. The current study aimed to investigate the effect of Borago officinalis L extract on serum testosterone levels, sperm parameters, in the streptozotocin (STZ)-induced mouse model of diabetes.